The labour constitution: the enduring idea of labour law - Dukes, Ruth (Oxford, 2017)
"By exploring different approaches to the study of labour law, this book re-evaluates how it is conceived, analysed, and criticized in current legislation and policy. In particular, it assesses whether so-called 'old ways' of thinking about the subject, such as the idea of the labour constitution, developed by Hugo Sinzheimer in the early years of the Weimar Republic, and the principle of collective laissez-faire, elaborated by Otto Kahn-Freund in the 1950s, are in fact outdated. It asks whether, and how, these ideas could be abstracted from the political, economic, and social contexts within which they were developed so that they might still usefully be applied to the study of labour law.